2019
DOI: 10.3390/md18010012
|View full text |Cite
|
Sign up to set email alerts
|

RgIA4 Accelerates Recovery from Paclitaxel-Induced Neuropathic Pain in Rats

Abstract: Chemotherapeutic drugs are widely utilized in the treatment of human cancers. Painful chemotherapy-induced neuropathy is a common, debilitating, and dose-limiting side effect for which there is currently no effective treatment. Previous studies have demonstrated the potential utility of peptides from the marine snail from the genus Conus for the treatment of neuropathic pain. α-Conotoxin RgIA and a potent analog, RgIA4, have previously been shown to prevent the development of neuropathy resulting from the admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 82 publications
(118 reference statements)
1
18
0
Order By: Relevance
“…A large number of studies using rodent dorsal root ganglion neurons or in vivo rodent models have been performed to elucidate the mechanisms of angialgia, such as those underlying paclitaxel-induced neuropathic pain. (17,18) However, these mechanisms are likely complex, and a quantitative evaluation of angialgia that represents the degree of pain caused by chemotherapy is difficult using conventional methods. Human evaluation of pain is confounded by the fact that it is a subjective phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies using rodent dorsal root ganglion neurons or in vivo rodent models have been performed to elucidate the mechanisms of angialgia, such as those underlying paclitaxel-induced neuropathic pain. (17,18) However, these mechanisms are likely complex, and a quantitative evaluation of angialgia that represents the degree of pain caused by chemotherapy is difficult using conventional methods. Human evaluation of pain is confounded by the fact that it is a subjective phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inhibiting the α9α10 receptor with the selective antagonist α-conotoxin RgIA reduced the severity of inflammation in the DSS model of colitis in mice [118]. RgIA and its analogs have been shown to have disease-modifying effects in a number of neuropathic and inflammatory disease models including sciatic nerve injury, diabetic neuropathy, and neuropathies associated with the use of the anti-cancer drugs paclitaxel and oxaliplatin [119][120][121][122]. An important mechanism through which RgIA exerts the observed therapeutic effects is by inhibiting the recruitment of lymphocytes and macrophages to damaged nerve tissues, although the exact mechanisms by which this occurs are currently unknown.…”
Section: Nicotinic Acetylcholine Receptor Subunits α9 and α10 Are Novel Players In Ibdmentioning
confidence: 99%
“…In addition to the aforementioned, many other drugs have been identified to reduce PIPN via several therapeutic targets, such as glutamate nerve systems [65,66], phosphodiesterase (PDE) [67,68], opioid receptors [72], acetylcholine receptor [77][78][79][80], cAMP/protein kinase A (PKA) signal [40], protein kinase C (PKC) [62,81], mitogen-activated protein kinase (MAPK) [28,39,49,53,56,[81][82][83], organic anion-transporting polypeptide 1b2 (OATP1B2) [84], mammalian target of rapamycin (mTOR) [51], and others [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103], at the pre-clinical research level.…”
Section: Othersmentioning
confidence: 99%